Application of Nanotechnology in Orthodontic Materials: A State-of-the-Art Review - Alberto De Stefani; Giovanni Bruno; Giorgia Preo; Antonio Gracco (MDPI AG, 2020)
Nanotechnology refers to the science that manipulates matter at molecular and atomic levels, and studies matter at the nanoscale level to detect and exploit the useful properties that derive from these dimensions; materials with components less than 100 nm in at least one dimension are called nanomaterials. Nanotechnology is applied in many fields, such as medicine (nanomedicine) and dentistry (nano-dentistry). The purpose of these innovations and research in this field is to improve human life and health. This article aims to summarize and describe what the most recent and known innovations of nanotechnology in dentistry are, focusing on and paying particular attention to the branch that is orthodontics, and on the application of new nanomaterials in the realization, for example, of orthodontic elastomeric ligatures, orthodontic power chains, and orthodontic miniscrews. We also address a very important topic in orthodontics, which is how to reduce the friction force.